Nilai Estetika Sajak “Sisa-SisaUsia” Karya Soedjarwo dan “Sajak Orang Tua” Karya Rahmat Djoko Pradopo - Muzakka, Moh (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The aesthetic study of poetry or poetry written by two authors is very rare, especially the two verses were compared to search for aesthetic concepts and trace their intertextual relationships. This short article attempts to describe and compare the aesthetic value of poem “ Sisa-Sisa Usia” by Soedjarwo and